Character Values Represented in Tembang Sunda Cianjuran - Aprilla Adawiyah; Mia Fatimatul Munsi (Indonesian Language Education and Literature, 2019)
This study is aimed at describing character values in five Cianjuran Sundanese songs (Tembang Sunda Cianjuran) comprising Laut Kidul, Mairan ti Dapur Yayasan Wargi Cianjur, Itu Gunung Naon Raden, Pamoyanan, and Kidung Wiwitan, taken from a book entitled Ngauguar Mamaos Cianjuran. These songs were chosen due to their lyrics which are easily understandable, full of character values and highly related to the locality of Cianjur. This article is based upon the analytic Descriptive method with a literature review used to examine and describe character values in Tembang Sunda Cianjuran. From eighteen character values, only thirteen character values are found in the songs. They are religiosity, honesty, discipline, hard work, creativity, curiosity, national spirit, patriotism, appreciation of achievement, communication, reading habits, environmental care, and responsibility values. In the current songs, the most frequently occurring value is patriotism, which is contained in the second song (TSC-02). It has nine character values. Cianjuran Sundanese songs function as the guiding norm of life, related to religion, and contains advice so that humans could behave in compliance with religion, the human and Creator relationship, as well as the human and environment relationship.Â Studi ini bertujuan mendeskripsikan nilai-nilai karakter dalam lima tembang Sunda Cianjuran yang terdiri atas Laut Kidul, Mairan ti Dapur Yayasan Wargi Cianjur, Itu Gunung Naon Raden, Pamoyanan, dan Kidung Wiwitan, yang diambil dari buku Ngaguar Mamaos Cianjuran. Tembang-tembang tersebut dipilih karena liriknya lebih mudah dipahami, mengandung nilai karakter, dan berkaitan erat kaitannya dengan lokalitas Cianjur. Metode yang digunakan adalah metode deskriptif analitik dengan teknik telaah pustaka untuk menelaah dan mendeskripsikan nilai-nilai karakter dalam tembang Sunda Cianjuran. Dari 18 nilai karakter, hanya 13 nilai karakter yang terdapat dalam tembang tersebut, berupa nilai religius, nilai jujur, nilai disiplin, nilai kerja keras, nilai kreatif, nilai rasa ingin tahu, nilai semangat kebangsaan, nilai cinta tanah air, nilai menghargai prestasi, nilai komunikatif, nilai gemar membaca, nilai peduli lingkungan, dan nilai tanggung jawab. Nilai karakter yang paling sering muncul adalah nilai cinta tanah air. Tembang Sunda Cianjuran memiliki fungsi bagi masyarakat sebagai salah satu acuan dalam kehidupan di dunia, berkaitan dengan agama, dan berisi nasihat agar manusia berperilaku sesuai dengan ajaran agama, berkaitan dengan hubungan manusia dengan sang Maha Pencipta, hubungan manusia dengan manusia, dan hubungan manusia dengan alam/lingkungan.